Stress and its Relation To Hair Loss Among Medical Students in a Tertiary Care Hospital of Kathmandu - Jha, Saurav; Goit, Dipesh; Sharma, Subhash Chandra (Nepal Journal of Dermatology, Venereology & Leprology, 2026)
Background: Students of the medical profession exhibit elevated levels of stress due to the modality of their academics. Due to stress, resources are diverted for flight & fight response and causes the release of cortisol. Both of these factors can lead to hair loss. Thus, it emphasizes the need for focused research in this group. This study aims to determine the prevalence of hair loss and its relation to stress among medical students. Materials and Methods: A cross-sectional study was conducted among undergraduate medical students of Kathmandu Medical College Teaching Hospital from December 2021 to March 2022. Ethical approval was obtained from the Institutional Review Committee. 216 students were selected using a non-probability convenience sampling method. Perceived stress scale was used to assess the level of stress and hair pull test was used to assess the degree of hair loss. Results: A total of 216 students including 91 females and 125 males participated in the study. Mean age was 21.7 ± 1.6 years. 15.75% of students (12 females; 22 males) had low stress, 58.33% of students (45 females; 81 males) had moderate stress and 25.93% of students (34 females; 22 males) had severe stress. A total of 30 (13.88%) students had excessive hair loss. Among them 11 were males and 19 were females. Hair loss was more prevalent in females (20.87%) as compared to males (8.8%). Multivariate logistic regression adjusting for stress levels showed that male students had significantly higher odds of hair loss compared to females (AOR = 2.746, 95% CI: 1.210–6.231, p = 0.016). There was no statistically significant association between stress and hair loss among medical students (χ² = 0.969, df = 2, p = 0.616). This finding was confirmed by multivariate logistic regression adjusting for gender (Wald χ² = 0.698, df = 2, p = 0.705) Conclusions: Hair fall is not common among medical students of Kathmandu Medical College Teaching Hospital, and no significant association was found between stress and hair fall.